Religion, politics, and communalism : the South Asian experience - Chatterji, Rakhahari, 1943- (New Delhi : South Asian Publishers, 1994)
Contributed articles.
Keywords: Religion and politics -- India; Communalism -- India; India -- Politics and government -- 1977-